Analisis Transformasi Sosial-Budaya dalam Tradisi Kondangan: Studi Kasus di Desa Cilimus, Kuningan, Jawa Barat - Rahman, Muhammad Ihsan Aulia; Azmi Ali Yafie (Prodi Sosiologi Agama, 2023)
This research aims to understand the socio-cultural transformation of the kondangan tradition in the Kuningan community, focusing on a case study in Cilimus Village. The kondangan tradition has an important role in Sundanese culture as a social gathering place, a symbol of togetherness and the customs contained therein. However, social development and changing values in society can have an impact on this tradition. Therefore, this research was conducted to explore the changes that occurred in the kondangan tradition in Cilimus Village and the factors that influenced it. The research method used in this study is qualitative research with a case study approach. Data were collected through observation, interviews with conductors and participants, and document studies related to the tradition of kondangan in Cilimus Village. The collected data were analyzed thematically to identify patterns of change in the kondangan tradition and the factors that influence it. The results of this study indicate that the main change is the increased use of technology in the kondangan tradition. This change occurred as a result of digitization and the domino effect of covid-19. It can be seen that many people use invitations sent via social media and messaging applications. This makes the invitation process more efficient and environmentally friendly, but it also changes the dynamics of social interaction in kondangan. In addition, social and economic changes also affect the kondangan tradition. So this research provides valuable insights into the kondangan tradition as a whole. As well as understanding cultural changes and maintaining their traditional identity to deal with ongoing changes.